Analisis Kualitas Air Baku dan Kualitas Air Hasil Produksi pada Instalasi Pengolahan Air (IPA) Unit Mukok PDAM Tirta Pancur Aji Kota Sanggau - Atikah, Ummi; Purnaini, Rizki; Asbanu, Govira Christiadora (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
The PDAM Tirta Pancur Aji Water Treatment Plant (WTP) Unit Mukok has a capacity of 10 liters/second which serves of the need clean water in the Mukok District. The water produced by the WTP Unit Mukok visually looks cloudy with impurities floating on the surface of the water. The purpose of this research is to whether the raw water rate for the parameters pH, temperature, turbidity, color and total amount of coliform complied with PP No. quality standards. 49/2010 as drinking water. The research method used is sampling and water quality testing. The results showed on the current conditions of the Mukok IPA unit, as a raw water source the Kapuas River has a quality of pH 8, temperature 28 °C, turbidity 34.9 NTU, color 224 PtCo. and a total of 25 MPN. The quality of the produced water is pH 7,3, temperature is 28 ° C, turbidity is 23.52 NTU, color is 4.19 PtCo, and total coliform is 10 MPN. The analysis showed that the raw water fraction does not correspond to class I in terms of turbidity and color parameters water standards PP No. 22 of 2021, the analytical results of the rate of the produced water show the turbidity and coliform parameters do not correspond to the standard of Permenkes No. 492 of 2010.